Temporary mechanical circulatory support with the iVAC 2L transaortic device in high-risk percutaneous coronary intervention — a multicenter experience - E. A. Avetisyan; O. B. Dorogun; E. V. Krasnoperova; R. S. Tarasov; V. I. Ganyukov; A. E. Baev; L. G. Shestakova; O. L. Polonetsky; V. V. Bazylev; M. E. Evdokimov; M. G. Shmatkov; D. V. Pevzner (Российский кардиологический журнал)
Aim. To analyze the multicenter international experience of high-risk protected percutaneous coronary intervention (PCI) procedures using the transaortic temporary pulsatile mechanical circulatory support (MCS) device iVAC 2L (PulseCath B. V., Amsterdam, the Netherlands).Material and methods. The pilot prospective-retrospective international multi-center observational study included patients with multivessel and/or complex coronary lesions, indications for coronary revascularization and refusal of the heart team from coronary artery bypass grafting and unprotected PCI due to a high risk of complications. PCI was performed with a temporary MCS using the iVAC 2L device in five clinics in Russia and Belarus.Results. From February 2023 to February 2024, 24 patients were included in the study. The median age was 69,0 years (interquartile range (IQR): 63,5-71,8); 87,5% were men. Twenty patients (83,3%) underwent elective PCI and four patients (16,7%) due to acute coronary syndrome (ACS) as follows: three with non-ST-segment elevation myocardial infarction and one with ST-segment elevation myocardial infarction (STEMI). The patient with STEMI underwent PCI against the background of acute heart failure (AHF). The median MCS time was 66,0 min (IQR: 43,0-98,0). Technical success of PCI was achieved in 100% of patients. The median initial and residual SYNTAX scores were 35,0 (IQR: 25,6-41,4) and 8,0 (IQR: 5,0-17,5), respectively. The median left ventricular ejection fraction before PCI and 7 days after was 44,0% (IQR: 31,0-54,0) and 48,0% (IQR: 36,5-53,5), respectively. In two cases (8,3%), major bleeding from the access site of the MCS device was observed. There were 2 fatal outcomes as follows: during elective PCI due to progression of acute left ventricular failure and in the late period due to septic shock after emergency PCI.Conclusion. PCI with MCP by the iVAC 2L device is an applicable and relatively safe tactic of coronary revascularization in patients with a high risk of complications, including in the conditions of ACS and AHF.